2023
DOI: 10.3390/s23041877
|View full text |Cite
|
Sign up to set email alerts
|

Marine Structural Health Monitoring with Optical Fiber Sensors: A Review

Abstract: Real-time monitoring of large marine structures’ health, including drilling platforms, submarine pipelines, dams, and ship hulls, is greatly needed. Among the various kinds of monitoring methods, optical fiber sensors (OFS) have gained a lot of concerns and showed several distinct advantages, such as small size, high flexibility and durability, anti-electromagnetic interference, and high transmission rate. In this paper, three types of OFS used for marine structural health monitoring (SHM), including point sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 167 publications
0
10
0
Order By: Relevance
“…An FBG sensor can reflect the spectrum of incident light with a specific wavelength [ 41 ]. According to the coupled-mode theory of the optical fiber, the Bragg wavelength is given as follows: where denotes the effective refractive index, and Λ denotes the grating period.…”
Section: Methodsmentioning
confidence: 99%
“…An FBG sensor can reflect the spectrum of incident light with a specific wavelength [ 41 ]. According to the coupled-mode theory of the optical fiber, the Bragg wavelength is given as follows: where denotes the effective refractive index, and Λ denotes the grating period.…”
Section: Methodsmentioning
confidence: 99%
“…This highlights the importance of monitoring strain and temperature variations to assess the structural health and performance of historic buildings. In additional, Chen et al [42], SHM of the Temple of Confucius was conducted using distributed optical fibre sensing technology and wireless sensor networks. The study demonstrated the effectiveness of the sensors in detecting and quantifying the presence of cracks in the building's walls.…”
Section: Cracks Due To Temperaturementioning
confidence: 99%
“…With 10 graphene layers, the sensor achieved a sensitivity of 2810 nm/RIU. The sensing apparatus has the potential for use in portable biosensors for various biological and chemical sensing applications [1].…”
Section: Surface Plasmon Resonance (Spr) Based Sensing Devicesmentioning
confidence: 99%
“…With 10 graphene layers, the sensor achiev sensitivity of 2810 nm/RIU. The sensing apparatus has the potential for use in por biosensors for various biological and chemical sensing applications [1]. Two-dimensional materials, such as graphene, transition metal dichalcoge (TMDs), and black phosphorus, offer several advantages that can improve the sensi of sensors [72][73][74].…”
Section: Surface Plasmon Resonance (Spr) Based Sensing Devicesmentioning
confidence: 99%
See 1 more Smart Citation